Changes in inflammatory cytokine networks in myasthenia gravis - Uzawa, Akiyuki (Sci Rep, 2016)
Myasthenia gravis (MG) is an autoimmunological inflammatory disorder of the neuromuscular junction. Inflammation could be a key player for understanding the pathogenesis of MG. We measured the serum levels of 24 inflammatory cytokines in 43 patients with anti-acetylcholine receptor antibody-positive MG and 25 healthy controls. In patients with MG, serum levels of a proliferation-inducing ligand (APRIL), IL-19, IL-20, IL-28A and IL-35 were significantly increased as compared with controls (p < 0.05). Among them, IL-20, IL-28A and IL-35 were significantly decreased after treatment (p < 0.05). In clinical subtype analyses, APRIL and IL-20 were increased in patients with late-onset MG and IL-28A levels were increased in patients with thymoma-associated MG compared with healthy controls (p < 0.01). The results of the present study demonstrate both anti-inflammatory and inflammatory cytokines are upregulated in MG, reflecting the importance of cytokine-mediated inflammation and its regulation in MG pathophysiology.